Development of automatic adjustment rear view mirror - Baharan, Mohd Redzuan bin; Aziz, Mohd Khairul Faiezi; Ahmad, Salmiah (2013)

(untitled)
Automatic adjustment rear view mirror system is designed to constitute for the weak points of the manual adjustment rear view mirror. This system determines the optimal position angle of the rear view mirror based on height of the driver, categorised as short, medium and tall. To achieve this target, the driver’s face coordinates are measured by means of an image processing technique. These coordinates are input to a mirror actuation system which rotates the mirror to the target position. This system is very easy, convenient and safe to use, and it is possible to adjust mirrors safely while driving since all processes are performed automatically.